Working in the food service industry - British Columbia Cook Articulation Committee; BC Open Textbook Project; BCcampus (BCcampus, BC Open Textbook Project, 2014)
"Working in the Food Service Industry is one of a series of Culinary Arts books developed to support the training of students and apprentices in British Columbia's food service and hospitality industry. Although created with the Professional Cook, Baker, and Meat Cutter programs in mind, these have been designed as a modular series, and therefore can be used to support a wide variety of programs that offer training in food service skills.Working in the Food Service Industry covers B.C. legislation and regulations for employment standards, as well as an overview of the "soft skills" of communication, conflict resolution, teamwork, and career planning"--BC Campus website.
This work is licensed under the Creative Commons Attribution-NonCommercial-ShareAlike License.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Description based on online resource; title from pdf title page (viewed on January 7, 2016).
Keywords: Food service -- Textbooks; Electronic books